Analisis Framing Pesan Moral Dalam Film Buya Hamka Vol. 1 - Muhammad Ananda; Choiriyah Choiriyah; Jawasi Jawasi (Social Science and Contemporary Issues Journal, 2024)
Film is the most effective mass communication media in delivering messages because it is able to combine audio and visual elements. Movies can provide good effects from educational, affective and cognitive aspects, these effects can be conveyed easily and interestingly to the audience. Movies not only tell a story, but also convey certain messages to the audience. Buya Hamka Vol 1 depicts the life journey of Buya Hamka, a scholar, writer, and figure in the Indonesian independence movement. This film tells the story of Buya Hamka's preaching journey, until his difficult times during the Japanese occupation. This film is the work of Fajar Bustomi who managed to attract the attention of the audience, this film also achieved great success with the number of viewers reaching 1 million people within two weeks of screening. With the various advantages of this film, the author conducts in-depth research on the story aspects of this film, in order to understand what issues and messages are actually being conveyed. In this study, I want to reveal and analyze the content of the Buya Hamka Vol 1 film story directed by Fajar Bustomi. Through the exploration of various aspects in this film, including characters, dialog, scenes and messages that the director wants to frame. By using Pan and Kosicki's framing analysis theory, it can be examined how the process of delivering messages and packaging messages by the director through syntactic, script, thematic, and rhetorical elements according to the message issues highlighted in the frames contained in the film's story. This research adopts a qualitative approach because it emphasizes text interpretation rather than category grouping. Data were collected through research documents and analyzed using Pan and Kosicki's structural framing model. A conclusion can be drawn, that by analyzing the film through the framing theory approach and its structure, it can reveal the message issues that the director wants to convey to the audience. From the results of the frame analysis of the Buya Hamka Vol 1 film, a message containing elements of goodness (moral message) is revealed.